30 Years of WrestleMania - Miller, Dean, 1969- (Indianapolis, IN DK/Brady Games, 2014)
Celebrate 30 years of WrestleMania! 30 years of WrestleMania provides amazing in-depth coverage of WWEs Wrestlemania from its inception right up to the present day.--provided by publisher.
Keywords: Wrestling matches -- History; Wrestlers -- Anecdotes